PENGGUNAAN KATA AISHITERU DAN SUKI PADA TINDAK TUTUR PENGUNGKAPAN CINTA DRAMA JEPANG - Vini Vistiade; Zuli Laili Isnaini; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The reasearch is discussed about the use of the word aishiteru and suki as a expression of love in Japanese. This research aimed to determine the use of aishiteru and suki words contained in speech acts of expression love Japanese drama. The object of this research is the Japanese drama entitled Itazura Na Kiss(Love in Tokyo) and 5Ji Kara 9Ji Made. This research is a descriptives qualitative research method using pragmatic theory and aspects of speech by Leech. Data collection method was “simak” method, “sadap”, “simak bebas libat cakap”, record and taking note technic. Data were analyzed by using padan technique and Pragmatic pranic techniques. The result shows that 30 data containing the expression of love using aishiteru and suki words. From 30 data is taken 12 data as material of data analysis. The result of the research shows that there are different usage of aishiteru and suki. Suki more often and commonly used by Japanese people to express love because of its vague and does not force the opponent's will. While aishiteru is used to express a more serious love like marriage. Aishiteru and suki are used in the form of direct and indirect speech according to context.Keywords: Use, aishiteru, suki, pragmatik, speech acts